Composition of government investment in Europe: Some forensic evidence - Juan Gonzalez Alegre; Andreas Kappeler; Atanas Kolev; Timo Välilä (EIB Papers, 2008)
We set out to decompose government investment, seeking especially to estimate how much governments in Europe invest in infrastructure in general and transport infrastructure in particular. It is concluded that infrastructure accounts for about one-third of overall government investment in the EU on average, with the share of transport investment as high as 80 percent in government infrastructure investment. These shares have remained quite stable in the past decades, so government transport investment has not suffered from excessive swings, slides or sudden stops - at least relative to other types of government investment. Whether that has been economically optimal is an altogether different issue, to be addressed elsewhere.
Keywords: 330; Öffentliche Investition; Infrastrukturinvestition; Verkehrsinvestition; EU-Staaten